Molecular Docking Analysis of Soft Coral (Rhytisma sp.) Derived Compounds as EGFR Inhibitors in Non-Small Cell Lung Cancer (NSCLC) - Rozikin; Tri Wahyu Setyaningrum; Widie Kemala Hapsari; Ozie Akbar Pratama; Gravinda Widyaswara; Mursal Ghazali; Novita Tri Artiningrum (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
The epidermal growth factor receptor (EGFR) is a crucial target in the treatment of non-small cell lung cancer (NSCLC) due to its significant role in tumor cell proliferation and survival. This study investigates the potential of marine-derived compounds from soft coral (Rhytisma sp.) as EGFR inhibitors through molecular docking and pharmacokinetic predictions. Eight compounds identified via GC-MS were docked against the EGFR tyrosine kinase domain (PDB ID: 2ITY) using AutoDock Vina, with Gefitinib serving as the reference drug. The top-performing compounds exhibited binding affinities ranging from –7.0 to –7.4 kcal/mol, closely aligning with Gefitinib's affinity of –7.6 kcal/mol. Notably, 4,12,12-trimethyl-9-methylidene-5-oxatricyclo[8.2.0.0⁴,⁶]dodecane demonstrated the strongest interactions, involving critical residues such as MET793 and LYS745. Pharmacokinetic profiling conducted with SwissADME and pkCSM confirmed favorable drug-likeness and high absorption potential. Toxicity analysis using ProTox-3.0 indicated low toxicity (Class IV) and no predicted hepatotoxicity, carcinogenicity, or mutagenicity. These findings suggest that phytocompounds derived from Rhytisma sp., particularly terpenoid-based structures, present a promising scaffold for the development of EGFR-targeted anticancer drugs.